Implementation of Early Childhood Education Kits in Higher Education Student Learning: Ex-post Facto Study of Open University Students - Nur Widhi, Ernayanti; Amini, Mukti (Program Studi Magister Pendidikan Anak Usia Dini, 2024)
The ECE kit is practical and has benefits in the lecture process for The Open University ECE Bachelor's study program, which aims to produce professional ECE teachers who can work globally. This research aims to see the results of implementing the ECE kit 2023 from the perspective of students as ECE kit users. This research is an ex-post facto research with 890 student participants who completed the ECE kit implementation questionnaire. The results of the research show that the use of the ECE kit can liven up the learning atmosphere in the classroom. The use of ECE kits as effective media in student teaching practice classes has an impact on learning outcomes. Most students who use ECE kits (52.4%) strongly agree that it is easier for students in their class to understand learning themes if they use ECE kits. Also, 60.1% of students strongly agreed that using ECE kits made students more enthusiastic—teaching practice students. Students in teaching student classes are motivated and enthusiastic about participating in learning with the APE in the ECE kit. Keywords: early childhood education, learning kits, higher education students, open university References: Apriani, R. (2019). The Effect of Learning Media and Interest In Learning on English Learning Outcomes. English Journal, 13(2), 68. https://doi.org/10.32832/english.v13i2.3780 Beale, J. (2020). Educational neuroscience and educational neuroscientism. In The ‘BrainCanDo’ Handbook of Teaching and Learning (pp. 17–32). David Fulton Publishers. https://doi.org/10.4324/9780429197741-1 Chandrawati, T. (2018). How Online Tutorial can Help Distance Education Students to be more Active in Their Learning. Proceedings of the 4th International Conference on Early Childhood Education. Semarang Early Childhood Research and Education Talks (SECRET 2018). https://doi.org/10.2991/secret-18.2018.24 Doliente, C. J. O., Tual, D.-X., Paglinawan, Z. B., Naparan, J. A., & Facunla, H. L. (2023). Exploring Students’ Utilization of Online Public Access Catalog in the Learning Common. 29–37. Dryden, W., & Neenan, M. (2020). Facing Adversity Sensibly when Carrying out Homework Assignments. In Rational Emotive Behaviour Therapy (pp. 183–185). Routledge. https://doi.org/10.4324/9781003132493-70 Dwi, A. (2021). Ketersediaan dan Pemanfaatan Alat Permainan Edukatif (APE) di Taman Kanak-Kanak Gugus Sido Mukti Mantrijeron Yogyakarta. E Journal PGPAUD UNY, 10(2), 159–163. Fuentes, K. C. (2020). The Tutorial Action in University Accounting Students. International Journal of Early Childhood Special Education, 12(1), 478–487. https://doi.org/10.9756/int-jecse/v12i1.201028 Hartwig, M. K., & Dunlosky, J. (2017). Category learning judgments in the classroom: Can students judge how well they know course topics? Contemporary Educational Psychology, 49, 80–90. https://doi.org/10.1016/j.cedpsych.2016.12.002 Hasanah, U. (2019). Penggunaan Alat Permainan Edukatif (APE) pada Taman Kanak-kanak Se-Kota Metro. AWLADY : Jurnal Pendidikan Anak, 5(1), 20. https://doi.org/10.24235/awlady.v5i1.3831 Hekmatiar, Y., & Umam, C. (2020). Effects of Learning Media And Vocabulary Mastery Towards Reading English Text Skill. Journal of English Language Teaching and Literature (JELTL), 3(1), 33–40. https://doi.org/10.47080/jeltl.v3i1.784 Helgetun, J. B., & Decuypere, M. (2023). One thing can be more than one thing: a comparative study of the teacher professionalization app ‘TeacherTapp.’ Learning, Media and Technology, 1–16. https://doi.org/10.1080/17439884.2023.2226876 Kamaliya, D. H., Tukiran, & Indana, S. (2022). Profile of Electronic and Digital Media Learning Implementation During 2018-2022. IJORER : International Journal of Recent Educational Research, 3(3), 354–363. https://doi.org/10.46245/ijorer.v3i3.213 Kulsum, U. (2021). Hybrid Learning Time Modification Can Improve Learning Activity And Learning Outcomes. SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 11(3), 263–268. https://doi.org/10.24114/sejpgsd.v11i3.27922 Muhammad, H. N., Hidayat, T., Ridwan, M., & Wibowo, S. (2022). The Effect of Stop Motion Learning Media on Learning Motivation. AL-ISHLAH: Jurnal Pendidikan, 14(3), 4637–4644. https://doi.org/10.35445/alishlah.v14i3.2264 Mweene, P., & Muzaza, G. (2020). Implementation of Interactive Learning Media on Chemical Materials. Journal Educational Verkenning, 1(1), 8–13. https://doi.org/10.48173/jev.v1i1.24 Nurkanti, M., Utari, T. S. G., & Devi, C. (2018). Improve Student Learning Outcomes Through The Use of Interactive Visual Learning Media (MIVI). Improving Educational Quality Toward International Standard. https://doi.org/10.5220/0008679500640068 Nurwidaningsih, L., Hastuti, I., & Rohmalina, R. (2019). Upaya Meningkatkan Pembelajaran Sains Melalui Permainan Terapung dan Tenggelam Dengan Media Telut pada Kelompok A. CERIA (Cerdas Energik Responsif Inovatif Adaptif), 2(5), 210. https://doi.org/10.22460/ceria.v2i5.p210-215 Pakhomova, T., Kan, D. S., Uriadova, V., Vasylchuk, V., & Vasylchuk, L. (2020). Information Technologies and Teaching Aids for Distance Learning in Educational Institutions under Quarantine. Universal Journal of Educational Research, 8(11D), 69–76. https://doi.org/10.13189/ujer.2020.082409 Permatahati, D. R., & Wangid, M. N. (2019). The Application of Murder Model with Image Media to Improving Student Learning Outcomes at the Fourth Grade Students. International E-Journal of Educational Studies, 3(6), 174–180. https://doi.org/10.31458/iejes.604883 Rosalianisa, R., Purwoko, B., & Nurchayati, N. (2023). Analysis of Early Childhood Fine Motor Skills Through the Application of Learning Media. IJORER : International Journal of Recent Educational Research, 309–328. Sahronih, S., Purwanto, A., & Sumantri, M. S. (2019, March). The Effect of Interactive Learning Media on Students’ Science Learning Outcomes. Proceedings of the 2019 7th International Conference on Information and Education Technology. https://doi.org/10.1145/3323771.3323797 Sari, W., Utomo, E., & Kustandi, C. (2019). Pengembangan Instrumen Analisis Kinerja untuk Tutor Online di Fakultas Keguruan dan Ilmu Pendidikan Universitas Terbuka. Jurnal Pembelajaran Inovatif, 2(2), 90–95. https://doi.org/10.21009/jpi.022.02 Shane-Simpson, C., & Bakken, T. (2022). Students’ Fear of Missing Out Predicts In-Class Social Media Use. Teaching of Psychology, 51(2), 141–150. https://doi.org/10.1177/00986283211060752 Sugiyono. (2010). Quantitative, Qualitative and R&D Research Methods. Alfabeta. Urfiyati. (2020). Motivasi Belajar, Media Pembelajaran, Kemampuan Membaca Terhadap Hasil Belajar IPS. Jurnal Penelitian Dan Pendidikan IPS, 13(1), 14–21. https://doi.org/10.21067/jppi.v13i1.4747 Vitásková, K. (2019, November). Transdisciplinary Cross-Sectoral Competency-Based Academic Curriculum Design of Speech Language Therapy (Logopedics) Study Program Including Supervised Research- And Evidence-Based Activities. ICERI2019 Proceedings. https://doi.org/10.21125/iceri.2019.2862 Wafi, F., & Safri, M. (2023). The Importance Of Application Of Learning Media To The Process Of Student Development. International Journal of Students Education, 354–357.